Effects of different peracetic acid formulations on post space radicular dentin - Garcia Belizario, Laurie [UNESP]; Carlos Kuga, Milton [UNESP]; Mariana Castro-Nunez, Gabriela [UNESP]; Gustavo Escalante-Otarola, Wilfredo [UNESP]; Vinicius Reis So, Marcus [UNESP]; Ricardo Pereira, Jefferson (Elsevier B.V., 2018)
Statement of problem. The optimal irrigating solution with antimicrobial and dentin cleansing properties for post space preparation for fiber posts is unclear. Peracetic acid is one option but is available in various chemical formulations that require evaluation. Purpose. The purpose of this in vitro study was to evaluate dentin surface cleanliness based on the presence of a smear layer and the number of open dentin tubules. It also investigates the chemical composition of residues after canal irrigation with a 1% peracetic acid solution (PA) at low or high concentration of hydrogen peroxide during the preparation of intracanal fiber posts. Material and methods. After filling the root canals of 40 mandibular incisors, a rotary instrument was used for intracanal preparation to place fiber posts. The teeth were divided into 4 groups (n=10) according to the post space irrigation protocol as follows: CG (control): distilled water; NA (NaOCl): 2.5% sodium hypochlorite; LH: PA with low concentration of hydrogen peroxide; and HH: PA with high concentrations of hydrogen peroxide. After irrigation, the teeth were sectioned, and the intracanal dentin surface was subjected to analysis using energy dispersive spectroscopy to evaluate chemical composition and to scanning electron microscopy (x500) to evaluate the presence of the smear layer. The number of open dentin tubules was measured by scanning electron microscopy analysis (x2000) using photo-editing software. ANOVA and the Tukey test (alpha=.05) were used to evaluate the data, except for the presence of a smear layer, for which the Kruskal-Wallis and Dunn tests were used (alpha=.05). Results. The highest concentrations of oxygen in the dentin residues were detected in LH and HH (P<.05); CG and NA showed similar oxygen concentrations (P>.05). NA had a higher concentration of chlorine (P<.05), whereas LH had a lower amount of smear layer and a larger number of open dentin tubules than the other groups (P<.05). These were equivalent to each other (P>.05), except for HH, which also had a larger number of open dentin tubules than CG and NA (P<.05). Conclusions. PA 1% with a low concentration of hydrogen peroxide yielded a lower amount of smear layer and a larger number of open dentin tubules in the dentin of the post space when compared with PA 1% with a high concentration of hydrogen peroxide, despite maintaining a similar oxygen concentration in these dentin residues.